Penyuluhan Optimalisasi Drainase Pedesaan Sebagai Langkah Maju Menuju Lingkungan Yang Lebih Baik - Febrianto, Alief Farhan; Azmi, Muhammad Sholahuddin; Raharja, Danang Setiya; Machmoed, Soerjandani Priantoro; Raharja, Danang Setiya Raharja (Universitas Wijaya Kusuma Surabaya, 2024)
Plosasari village, located in the Puri Sub-district, Mojokerto regency, Jawa Timur, deals with a severe communal drainage system problem, including erosion and environmental pollution. This community service aims to provide counselling on village drainage optimization as a step towards a better environment. The methodology to realize this service starts with a preliminary survey to investigate the existing condition of the drainage channel, preparation of presentation material based on literature review and previous survey, and finally, the implementation of the seminar in the village hall. The counselling results show that people's knowledge about the importance of drainage increased, and practical solutions to tackle common drainage problems were successfully formulated, including good drainage infrastructure planning, integrated waste management, and smart technology. Some constraints to realize those solutions include the difficulty of gathering community members and the lack of waste disposal facilities. This counselling supports the achievement of Sustainable Development Goals, especially for target number 6th, which is about clean water and sanitation, and target number 11th, which is about sustainable cities and communities, by proposing innovative and collaborative solutions for rainwater management and village drainage system. This counselling result can be implemented in other villages facing similar problems to improve the health and environmental conditions in the community.